Attracting Aboriginal Youth to The Study of Business: Mentorship, Networking, and Technology - Tulk, Janice Esther; Doucette, Mary Beth; MacKenzie, Allan (Journal of Aboriginal Economic Development, 2016)
There is widespread recognition that Aboriginal Canada needs more community members with business training to work in economic development and management, particularly with the growing development of natural resources in Aboriginal territories and self-governance initiatives. Yet, only 12% of funded Aboriginal students pursue post-secondary education in business or commerce. Barriers to the pursuit of tertiary education include inadequate student preparation and career guidance, lack of funding, and attitudes surrounding the ability to do math. The Purdy Crawford Chair in Aboriginal Business Studies at Cape Breton University addresses these barriers via its program for Aboriginal youth, which combines mentorship, networking, and technology to facilitate the transition from high school to post-secondary studies and engage students in business education. This article outlines the model employed by the Purdy Crawford Chair and assesses the initiative in relation to relevant literature on mentorship and technology.